Connect-In-Place : startup disrupts socializing and learning during COVID-19 - Isaacs, Andrew M., (SAGE Business cases., 2021)
When two UC Berkeley students were unexpectedly forced to leave their classrooms and transition to online classes due to COVID-19 in spring 2020, they adjusted to a very new normal. However, due to shared experience championing educational equality, they realized that younger (K-12) students forced into online learning would likely suffer social isolation and reduced learning. So, the two undergrads brainstormed (remotely) about how a startup could tackle some of the new educational and emotional challenges that pre-college students would face due to pandemic restrictions.The first free session of Connect-In-Place (CIP) launched in June 2020 fulfilling the initial mission of building a learning community intended to ease isolation. After several pivots, by February 2021, CIP had built a small but global learning team. Key questions remained: Should CIP be organized as a for-profit company or as a nonprofit entity? How would a team of volunteer college students stay committed even while attending school full time? What opportunities and challenges lay ahead for CIP's business model? What impact was CIP having on whom, and how might that impact be measured?